Impact of extramedullary disease in patients with newly diagnosed multiple myeloma undergoing autologous stem cell transplantation: a study from the Chronic Malignancies Working Party of the EBMT - Nico Gagelmann; Diderik-Jan Eikema; Simona Iacobelli; Linda Koster; Hareth Nahi; Anne-Marie Stoppa; Tamás Masszi; Denis Caillot; Stig Lenhoff; Miklos Udvardy; Charles Crawley; William Arcese; et al. (Haematologica, 2018)
We investigated extramedullary disease in newly diagnosed multiple myeloma patients and its impact on outcome following first-line autologous stem cell transplantation. We identified 3744 adult myeloma patients who received up-front single (n=3391) or tandem transplantation (n=353) between 2005 and 2014 with available data on extramedullary involvement at diagnosis. The overall incidence of extramedullary disease was 18.2% (n=682) and increased per year from 6.5% (2005) to 23.7% (2014). Paraskeletal involvement was found in 543 (14.5%) and extramedullary organ involvement in 139 (3.7%). More patients with extramedullary organ involvement had multiple involved sites (≥2; P<0.001). In a comparison of patients with single sites with patients without the disease, up-front transplantation resulted in at least similar 3-year progression-free survival (paraskeletal: P=0.86, and extramedullary organ: P=0.88). In single paraskeletal involvement, this translated less clearly into worse 3-year overall survival (P=0.07) while single organ involvement was significantly worse (P=0.001). Multiple organ sites were associated with worse outcome (P<0.001 and P=0.01). First-line treatment with tandem compared with single transplantation resulted in similar survival in patients with extramedullary disease at diagnosis (P=0.13 for both).